Culture and the politics of Third World nationalism - Dawa Norbu, 1949- (Routledge, 1992)
Nationalism in specific political systems combined with a theoretical framework that draws out its universal significance. Ten case studies from South Asia, the Middle East, Latin America and Europe focus on local cultural factors.
Keywords: Developing countries -- Politics and government.; Nationalism -- Developing countries.; Political culture -- Developing countries.; Nationalisme -- Pays en voie de développement.; Culture politique -- Pays en voie de développement.; Pays en voie de développement -- Politique et gouvernement.; POLITICAL SCIENCE -- Political Process -- General.; Nationalism; Political culture; Politics and government; Developing countries; Nationalisme.; Culturele aspecten.; Developing countries -- Politics